Clinical and histopathological features of lupus nephritis and the risk of long-term kidney outcomes in Indonesia - Hustrini, Ni Made; Susalit, Endang; Miranda, Monik Ediana; Saraswati, Meilania; Teng, Y. K. Onno; van Diepen, Merel; Rotmans, Joris I. (Frontiers in Lupus, 2025)
ObjectiveRace and region-specific variables influence lupus nephritis clinical features and prognosis. We examined the clinicopathological presentation and long-term kidney outcomes of lupus nephritis in Indonesia.MethodsThis was a retrospective cohort study conducted from 1 January 2011 to 31 December 2021 on biopsy-proven lupus nephritis patients, corresponding to the International Society of Nephrology/Renal Pathology Society 2018 classification. Patients were followed until death, development of end-stage kidney disease, initiation of kidney replacement therapy, or end of study. The association between lupus nephritis class and kidney outcomes was analyzed using cumulative incidence plots. A linear mixed-model analysis was performed to assess the association between lupus nephritis class and kidney function decline.ResultsThis study included 268 patients, with a mean age of 28.7 + 8.5 years, and 94.8% were female. The main histopathological diagnosis was class IV (39.6%). The prescription rate of renin–angiotensin–aldosterone system (RAAS) inhibitors ranged from 0.5% in class VI to 37.4% in class IV (p = 0.138), while that of hydroxychloroquine usage ranged from 0% in class VI to 37.7% in class IV (p = 0.845). Class IV was associated with higher chronic and active lesions, including global (42.6%, p = 0.073) and segmental (41.1%, p = 0.009) glomerulosclerosis; segmental (43.1%, p < 0.001) and global (74.1%, p = 0.004) endocapillary hypercellularity; and sub-endothelial deposit (59.5%, p = 0.007). Over a median follow-up of 26 (IQR = 6.0–48.0) months, 16.4% of patients died, and 3.7% developed end-stage kidney disease or initiated kidney replacement therapy. Infection, including tuberculosis (9.1%), was the leading cause of death. Class IV was associated with a high mortality risk (HR 1.94, p = 0.028), a lower baseline estimated glomerular filtration rate (eGFR) compared with class I/II (β = −51.3, SE = 12.3, p < 0.001), and a less steep decline or even an increase in eGFR over time (β = 15.7, SE = 7.0, p = 0.026).ConclusionsThis cohort demonstrated a high prevalence of chronic lesions, low use of renin–angiotensin–aldosterone system inhibitors and immunosuppressive medications, and notable mortality. This study highlights the importance of timely detection on kidney involvement in SLE patients, routine use of renin–angiotensin–aldosterone system inhibitors, optimal prescription of immunosuppressive medications, and aggressive screening and prophylactic measures of infectious diseases should be encouraged to improve kidney outcomes in lupus nephritis patients in Indonesia.